Study guides

☆☆

Q: What is 3a plus 3?

Write your answer...

Submit

Related questions

6a-3

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

"a" plus "3a" is equal to 4a. (3a+a=4a). You already have 3 "a's" and then you add another "a."

4a + 3a = (4 + 3)a = 7a

3A + 9B = 3(A + 3B)

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

x^3 + ax + 3a + 3x^2 = (x^3 + 3x^2) + (ax + 3a) = x^2(x + 3) + a(x + 3) = (x + 3)(x^2 + a)

13a - 6 + a = 5a + 3 + 3a 13a + a - 5a - 3a = 3 + 6 6a = 9 6a/6 = 9/6 a = 3/2

-8a + 3a = (-8 + 3)a = (5)a = 5a

3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)

3(a+4) = 3a+12

This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)

a = 3

3a + 9 =3X(a + 3)

It is 6a + 4

a(b+3)+b(b+3)

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2

You would factor 3a + 9b as: 3(a+3b)

3a + 4 = 4a - 3 4 = a -3 (subtract 3a from each side) 7 = a (add 3 to both sides) a = 7

3(3a+b)

It is 3a(a+3) when factored

That factors to (b + 3)(a + c)

(x + 3)(a + b)

What is the solution of -2a plus 3a plus 5b

3a+5b+7a=